Educational Attainment and Household Standard of Living in Nigeria - Surat, Shabi. O; Ofodile, Modesta Chinyere; Toriola, Anu Keshiro; Adelaja, Adekule Olugbanga; Salami, Lateef (SAINTIS Publishing, 2022)
In developing countries and Nigeria in particular more and more educated people are wallowing in poverty due to diminishing standards of living. Despite the launch and re-launch of the universal Basic Education scheme by successive government in Nigeria since 1999, inequalities relatively to standards of living chances have remained little altered. This study makes use of annual time series data sourced from the world bank development index (WDI) covering the period of 1981 to 2017. Jarque-Bera Normality test, Unit root test, test for multicorrelation, cointegration test were used for the pre-test while the Fully Modified Ordinary Least Squares (FMOLS) approach was used for the estimation. The result shows that educational attainment (=0.029, t = 7.986, p 0.05) and formal education complementary skills ( = 0.00001, t = 3.752, p 0.05) exert a significant positive effect on household standard of living in Nigeria. Income redistribution ( =-0.019, t = -2.112, p 0.05) does not show any effect on household standard of living in Nigeria. The study submitted that educational attainment and formal education complementary skills contribute positively to household standard of living. The need to create job for secondary school leavers some of whom may not be interested in further education to enhance the secondary school return to education was recommended.